Analysis of deformed state structures of the kyiv metro running tunnels on a transition zone from spondylov’s clay to buchatskiy sands - Petrenko, V. D.; Huzchenko, V. T.; Tiutkіn, O. L.; Tiutkіn, D. V. (Science and Transport Progress, 2014)
Purpose. In the section of changes geotechnical conditions of spondylov’s clay to buchatskiy sands may have significant structural deformation of running tunnels. It is necessary to identify the cause of deformities develop ways to minimize and based modeling and calculations to prove the effectiveness of measures to reduce deformation.Methodology. To solve the analysis problem of the stress-strain state (SSS) of the system «structure array» it was conducted the numerical simulation using the finite element method (FEM). On the basis of the obtained results the graphs were constructed and the dependencies were determined. Findings. The presence of weak water-saturated soils in tray of the tunnel on an area of transition from spondylov’s clay to buchatskiy sand causes significant increasing in strain construction of tunnels and general vibration liquefaction in soil basis. Also change the physical and mechanical characteristics of soils within the frames of tunnels influences on the level of strain state of most frames. Improved strain state settings of tunnels in areas of change soil characteristics of the array (especially at the bottom of casing) can be achieved by chemical consolidation of weak soils. Composition of solutions for fixing the weak soils should be determined based on the study of grain size, porosity, and other parameters of physical and mechanical and physical and chemical characteristics of soils.Originality.The basic cause significant strain on transition zone from spondylov’s clay to buchatskiy sands is found, that is explained by saturated phenomenon vibration liquefaction basis under the tunnel.Practical value.The approaches to reduce the strain in the construction of running tunnels in the transition zone from spondylov’s clay to buchatskiy sands are developed, as well as in the area ofthe station «Glybochytska»the Kyiv Metro.